2017
DOI: 10.3390/ijms18071570
|View full text |Cite
|
Sign up to set email alerts
|

Differential miR-346 and miR-582-3p Expression in Association with Selected Maternal and Fetal Complications

Abstract: Several miRNAs are expressed in human gestational tissue, and some have been shown to be associated with placental dysfunction and complicated pregnancy outcomes. To investigate the roles of miR-346 and miR-582-3p in adverse obstetric events, we analyzed these 2 miRNAs in three samples (maternal blood, umbilical cord blood and placenta) obtained from pregnant women in four groups, including healthy control (n = 60), preeclampsia (n = 31), preterm delivery (n = 29) and small for gestational age (n = 19) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…MiR-33b and miR-375 were overexpressed during macrosomia, while miR-454 was overexpressed in blood of both low birth weight and macrosomic compared to normal birth weight offspring [83]. Aberrant miR-346 and miR-582 expression in cord blood were shown to be associated with foetal complications [54]. Taken together, these studies provide evidence that GDM induces dysregulated miRNA expression in offspring, which may predispose them to metabolic disease in later life.…”
Section: Gestational Diabetes and Foetal Microrna Expressionmentioning
confidence: 73%
See 3 more Smart Citations
“…MiR-33b and miR-375 were overexpressed during macrosomia, while miR-454 was overexpressed in blood of both low birth weight and macrosomic compared to normal birth weight offspring [83]. Aberrant miR-346 and miR-582 expression in cord blood were shown to be associated with foetal complications [54]. Taken together, these studies provide evidence that GDM induces dysregulated miRNA expression in offspring, which may predispose them to metabolic disease in later life.…”
Section: Gestational Diabetes and Foetal Microrna Expressionmentioning
confidence: 73%
“…Subsequently, other studies have reported differential miRNA expression during preeclampsia and importantly provide experimental evidence to support the involvement of these miRNAs in disease pathophysiology [51,52]. Altered miRNA expression has also been observed in other pregnancy complications such as macrosomia [53], preterm delivery and small for gestational age [54].…”
Section: Micrornas Pregnancy and Gestational Diabetesmentioning
confidence: 83%
See 2 more Smart Citations
“…The whole blood samples (control, n = 55; preeclamptic group, n = 33) were prepared as per our previous publication (Tsai et al . ). Briefly, total RNA was extracted from plasma by using a commercial column‐based system (Direct‐zol RNA Miniprep kit, Zymo, Irvine, CA, USA).…”
Section: Methodsmentioning
confidence: 97%